Determinants of outcome of abdominal trauma in an urban tertiary center - Solomon Agbroko; Adedapo Osinowo; Emmanuel Jeje; Oluwole Atoyebi (Nigerian Journal of Surgery, 2019)
Background: Abdominal trauma constitutes a significant cause of potentially preventable mortality. Therefore, knowledge of the determinants of outcome facilitates the development of rational treatment protocols for improving outcome. Objective: To identify the determinants of outcome in patients with abdominal trauma managed in a tertiary health center. Patients and Methods: This is a prospective study of consecutive patients presenting with abdominal trauma to our tertiary health center over a 12-month period. Data regarding patient demographics, injury mechanisms, type of organ injuries, treatment modalities, injury-to-intervention time, and outcomes were documented. The Injury Severity Scores and Revised Trauma Scores were determined. The data were analyzed using the Statistical Package for the Social Sciences version 20. Results: There were 76 patients, 66 males and 10 females, whose ages ranged from 15 to 66 years (mean of 32.9 ± 10 years). Thirty-one (40.2%) patients had blunt abdominal trauma whereas 45 (59.8%) patients had penetrating trauma. There was a mortality rate of 8% predominantly from blunt trauma as compared to penetrating abdominal trauma (12.9% vs. 4.4%). There was a statistically significant difference between survivors and nonsurvivors as regards the means of injury-to-intervention time (25.4 ± 36.4 vs. 67.5 ± 58.2, P = 0.007), the means of Injury Severity Scores (15.1 ± 27.9 vs. 23.7 ± 9.8, P = 0.008), and the presence of brain injury (50.0% vs. 5.6%, P = 0.029). Conclusion: This study has shown that delayed intervention, high Injury Severity Score, and associated significant brain injury were determinants of poor outcomes. Prompt intervention and postoperative management in intensive care definitely improve outcome.